PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF BERBASIS SMART APPS CREATOR PADA KELAS VII - Ida Fauziyyah; Wharyanti Ika Purwaningsih; Isnaeni Maryam (STKIP PGRI Situbondo, 2023)
Online learning requires teachers to be able to create innovation and creativity in the use of technology that can support online or distance learning processes that cannot be carried out face-to-face, while mathematics lessons really need a detailed explanation of the material. This research, using a method that is research development method (Research and Development). The method used in this study uses development research with the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. An interactive math learning media based on smart apps creator for class VII SMP which was held in class VII-G SMP Negeri 10 Purworejo with 32 students. The product test results showed a media validity score of 3.7 with a good category from media experts and a score of 3.58 with a good category from material experts. Media practicality test results obtained a percentage of 94% from the limited test and obtained a percentage of 80% from the wide test. The results of the effectiveness of learning media obtained a complete percentage of 87% of 32 students, there were 28 students who passed. These data indicate that the math learning media based on smart apps creator for class VII SMP developed in this study is categorized as feasible.